PASCA KEJADIAN LUAR BIASA CHIKUNGUNYA DI DESA SEMALI KECAMATAN SEMPOR KEBUMEN TAHUN 2009 - Mars Wijayanti, Siwi Pramatama; Octaviana, Devi (Kesmas Indonesia: Jurnal Ilmiah Kesehatan Masyarakat, 2010)
Chikungunya outbreak in Kebumen regency happened onDecember 2008until 2009 that infected 10 sub district including Sempor sub district. Semali village in Sempor sub districtwas one of village that had chikungunya outbreak on February 2009, and 117 people were infected. The aim of this research were to know description of knowledge, attitude and behavior of Semali community after chikungunya outbreak, and also investigation of mosquito larvae at house of respondents. Kind of this research was observational with cross sectional design. Data was obtained by questionnaire. Univariane analysis was conducted to know the description of each variable. Result of this research showed that respondent?s knowledge about chikungunya that included in good category was 57,8% whereas remainder was had category (42,2%). Respondent?s attitude to Chikungunya was good category 51,6% and 48,5% was bad category 62,5% of respondent?s behavior were good category in order to protect Chikungunya, and 31,2% were bad community of village should improve their knowledge , attitude and behavior to protect vactor bome disease such as Chikungunya and dengue hemorrhagic fever. Further research in molecular epidemiology should be done to gain better perspective about changing of primary vactor of Chikungunya from Aedes aegypti to Aedes olbopictus.